THE CONFIGURATION OF MASS LAY-OUT AND EXTERNAL SPACE EXPLOITATION OF FISHING VILLAGES Study objects: The Fishing Villages of Cilincing and Marunda in North Jakarta - Levina Levina (Riset Arsitektur (RISA), 2017)
Abstract- Cilincing and Marunda are two kampongs situated in the north of Jakarta, immediately bordering on the Java Sea. The existence of the fishing villages sketches the lives of these communities. They make their living out of catching fish and other produce, so the lives of the fishing community take place between water and land. This situation has led to their settlement differing from others in the urban kampong. The synergy stimulated by the water-based context has inspired the unique architectural features of these villages, in terms of planning the lay-out of the dwelling-places or residential area.This research study is a descriptive-comparative analysis of the exploitation of exterior space based on the configuration pattern of the mass lay-out of the fishing villages observed. The data collection technique consists of gathering the relevant physical data along with those covering related activities. The physical data have been obtained by way of field mapping and observation, while the data concerning activities have been collected through observation and interviews conducted with the respondents, namely the inhabitants of the Cilincing fishing village (RT 012) and of Marunda (RT 03). The data have been divided based on the major outdoor activities of the community involved (sea-faring and residing). Finally, a comparison has been drawn between the research results of these two villages.The findings indicate that the configuration of the mass lay-out in these two fishing villages has created a quality of exterior space exploitation that is different as well. The one that displays a scattered lay-out pattern has a large volume of exterior space at its disposal that is left unexploited by its inhabitants, both for sea-bound activities and residential land-bound ones. The propinquity of the mass has created exterior space that is more intimate in nature.Keywords: Configuration of mass lay-out, exterior space